Full field optical coherence tomography can identify spermatogenesis in a rodent sertoli-cell only model - Ranjith Ramasamy; Joshua Sterling; Maryem Manzoor; Bekheit Salamoon; Manu Jain; Erik Fisher; Phillip S Li; Peter N Schlegel; Sushmita Mukherjee (Journal of Pathology Informatics, 2012)
Background: Microdissection testicular sperm extraction (micro-TESE) has replaced conventional testis biopsies as a method of choice for obtaining sperm for in vitro fertilization for men with nonobstructive azoospermia. A technical challenge of micro-TESE is that the low magnification inspection of the tubules with a surgical microscope is insufficient to definitively identify sperm-containing tubules, necessitating tissue removal and cytologic assessment. Full field optical coherence tomography (FFOCT) uses white light interference microscopy to generate quick high-resolution tomographic images of fresh (unprocessed and unstained) tissue. Furthermore, by using a nonlaser safe light source (150 W halogen lamp) for tissue illumination, it ensures that the sperm extracted for in vitro fertilization are not photo-damaged or mutagenized. Materials and Methods: A focal Sertoli-cell only rodent model was created with busulfan injection in adult rats. Ex vivo testicular tissues from both normal and busulfan-treated rats were imaged with a commercial modified FFOCT system, Light-CT TM , and the images were correlated with gold standard hematoxylin and eosin staining. Results: Light-CT TM identified spermatogenesis within the seminiferous tubules in freshly excised testicular tissue, without the use of exogenous contrast or fixation. Normal adult rats exhibited tubules with uniform size and shape (diameter 328 ±11 μm). The busulfan-treated animals showed marked heterogeneity in tubular size and shape (diameter 178 ± 35 μm) and only 10% contained sperm within the lumen. Conclusion : FFOCT has the potential to facilitate real-time visualization of spermatogenesis in humans, and aid in micro-TESE for men with infertility.